Reporting military casualties in Nigerian newspapers: An analysis of operations against Boko Haram insurgents - Ndinojuo, Ben-Collins Emeka; Ihejirika, Walter; Okon, Godwin (Jurnal Studi Komunikasi, 2020)
The Boko Haram conflict has inflicted untold hardship to the peace and society of the Northeast region in Nigeria and surrounding countries. Within the Nigerian front, the military has been mandated to engage the insurgents and bring them to submission. Opinions on the position of the media in helping the government to bring the conflict to a conclusion were divided as reports emerged that newspaper articles have caused low morale within the military during combat. This study employed content analysis on four Nigerian newspapers, Daily Trust, Premium Times, The Nation and Vanguard to investigate how military casualties were reported from 2014-2016. The research was based on the Framing theory of the press. Findings showed that 185 reports mentioned 33 military casualties. There were no images of military casualties found in any of the reports, where mentions of military casualties were predominantly found in the body and concluding parts of articles. The study found no evidence to support the claim that media reports were to blame for soldiers not being able to confront the Boko Haram insurgents. This study recommends cooperations between the media and military to coordinate efforts to end the conflict.